Utilization of citrus microcarpa peels and papaya seeds as a natural coagulant for turbidity removal. Issue 1 (November 2021) - Dollah, Z; Masbol, N H; Musir, A A; Karim, N A; Hasan, D; Tammy, N J
Abstract: Coagulation and flocculation are an essential component of both the treatment of drinking water and the treatment of wastewater. The coagulant is one of the materials or substances that is added to the water to remove, stabilizes and causes colloidal particles to settle. Chemical coagulants such as aluminum sulphate (alum), ferric chloride, and synthetic polymers are the most commonly used coagulants in the industry due to their efficacy in turbidity removal. However, the use of chemical-based coagulants has had some negative impacts on human health and the environment, such as Alzheimer's disease, and has produced a high volume of toxic sludge. In order to reduce negative impacts, this led to the discovery of an alternative to the natural coagulant (plant-based) for drinking water treatment. The coagulant used in this study is a combination of fruit waste containing citrus microcarpa peels and papaya seed with a ratio of 80:20 and 40:60. In addition to determining the potential of the composite natural coagulant, the optimal dosage and the effect of the mixing duration are also studied in order to determine the best mixing duration for each stage of the coagulation-flocculation process. Laboratory-scale studies using jar test experiments were conducted on surface water to determine the percentage of turbidity removal. Fruit waste was collected from the UiTM Pulau Pinang cafeteria, dried in the oven for 24 hours at a temperature of 105°C. The optimum dosage of composite natural coagulant is 90 mg/L using an 80:20 ratio of citrus microcarpa peels and papaya seeds with 97% of turbidity removal. The optimum mixing time is determined where the fast mixing time is 180 rpm for 3 minutes, the slow mixing time is 20 minutes with 10 rpm and the settling time is 30 minutes. The study shows that citrus microcarpa peels and papaya seeds have the potential to become effective natural coagulants in the future.